Strategi Produksi Film Dokumenter “Before You Eat” sebagai Kampanye Penghentian Isu Perbudakan Modern - Langi, Brian; Kusumawati, Dyah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The issue of slavery is a problem faced by a number of countries, not only in the enslavement of crew members but until now there is modern slavery, namely human trafficking. The study aims to determine the production strategy of the documentary film "Before You Eat" as a campaign to stop the issue of modern slavery that occurs in Indonesia, this study uses the concept of Anthony G.Artis' documentary film production strategy. This research uses a qualitative research approach with a descriptive type of research. Meanwhile, data collection techniques through observation and in-depth interviews with the production team of the film "Before You Eat". The results of this study show the production strategy carried out by the production team of SBMI, GPID and Sorgori in making documentary films as a media campaign to stop the issue of modern slavery.